Marks of school mathematics: The experience narrated by pedagogy students in a formative context (Revista Contexto & Educação, 2024)
We conducted an exploratory research study with a group of approximately 66 Pedagogy students on their experiences with Mathematics in Basic Education. The data pertains to a task titled "Me and Mathematics," developed as part of the mandatory course "Mathematics: Content and Teaching," offered in the 6th semester during the second academic semester of 2022. Our objective was to identify memories of future teachers shared during their educational process and how these memories influence their perception of the discipline. Narrative served as the central method for data production and educational practice. There is consensus that the discipline acts as a "filter" for individuals, as it can reinforce negative attitudes and distances that contribute to the formation of certain myths.
Keywords: Initial Teacher Training; Written Narrative; Mathematics Education